Word‐Combination‐Based Measures of Phraseological Diversity, Sophistication, and Complexity and Their Relationship to Second Language Chinese Proficiency and Writing Quality. Issue 4 (23rd July 2022) - Hu, Renfen; Wu, Jifeng; Lu, Xiaofei
Abstract: This study investigated the relationship of a set of word‐combination‐based measures of phraseological diversity, sophistication, and complexity to second language (L2) Chinese proficiency and writing quality in comparison to that of a set of large‐grained topic‐comment‐unit‐based measures. Our dataset consisted of 101 assessed narratives produced by Korean learners of Chinese as a L2 at 3 proficiency levels. Multiple phraseological measures exhibited stronger correlations with quality ratings and/or larger effect sizes for proficiency than did the large‐grained topic‐comment‐unit‐based measures. Measures pertaining to language‐specific features, including topic‐comment‐unit‐based measures and phraseological measures based on language‐specific word combination types, exhibited stronger discriminative power for intermediate and advanced levels than for beginning and intermediate levels. Our results also revealed the importance of predicate‐related combinations in assessing L2 Chinese phraseological diversity and complexity. We discuss the implications of our findings for L2 Chinese writing research and L2 Chinese pedagogy. Abstract :